Numerical simulation of XCC pile penetration in undrained clay - Zhou, Hang (2021)
This paper presents large deformation analysis of X-section Cast-in place Concrete (XCC) pile (a type of non-cylindrical pile) penetration in undrained clay using the Coupled Eulerian-Lagrangian (CEL) numerical technique. The main objective of this study was to investigate the shape effect of XCC pile cross-section on the penetration mechanism, such as the plastic zone around pile shaft and stress developed in the soil. The discrepancy of the stress mechanism between the circular and XCC piles are captured. The results show that the shape effect has insignificant influence on the plastic zone surrounding penetrated XCC pile. The shape effect only influences of the radial stress distribution around a rough XCC pile, while it can be neglected for smooth interface case. In addition, the radial stress, radial stress gradient and vertical stress around the smooth XCC pile shaft in θ=0° profile is larger than the one in θ= 45° profile. Moreover, the radial stress near the ground surface in θ= 45° profile is nearly equal to zero, while the radial stress near the ground surface in θ=0° profile sharply increases with the increasing of soil depth. The presented analysis provided a basis for developing design method for XCC pile in the future.